Level of SARS-CoV-2 exposure post the CoronaVac vaccination in health workers at Dr. Saiful Anwar General Hospital, Malang - Bormasa, Pelpina; Santoso, Sanarto; Diyah, Nurima; Wahono, Cesarius Singgih; Retnoningsih, Dewi (Journal of Clinical Microbiology and Infectious Diseases, 2024)
Introduction. COVID-19 is considered a new emerging infection due to SARS-CoV-2. CoronaVac refers to an inactivated SARS-CoV-2 vaccine obtaining EUL (Emergency use listing) from BPOM RI and WHO. This vaccine was previously reported to exhibit good efficacy in generating protective antibodies against SARS-CoV-2. Nevertheless, health workers in Indonesia might pose a high risk of COVID-19 exposure, leading to mortality. This study aims to identify the level of SARS-CoV-2 exposure to the CoronaVac vaccination in health workers at Dr. Saiful Anwar General Hospital, Malang. Methods. This study implemented analytical observational research with a prospective cohort approach on health workers at Dr. Saiful Anwar General Hospital, Malang, who received the 2nd dose of vaccination dose with a 14-day interval. All study subjects were observed for 6 months by examining the level of exposure to SARS-CoV-2 obtained from the results of nasopharyngeal and oropharyngeal swab examinations of SARS-CoV-2 RT PCR examination. Categorical data were tested by using Chi-square or Fisher exact. Results. From 184 samples, the SARS-CoV-2 exposure indicated several outcomes: positive 57 (31 %) and negative 127 (69%). Severity degrees of COVID-19 disease were asymptomatic 17 (29.8%), mild 37 (64.9), moderate 3 (5.3%), severe 0 (0%), and there were no mortality cases. The time (duration) of exposure to SARS-CoV-2 post-CoronaVac vaccination indicated that the highest number of participants with positive RT-PCR swab results post-vaccination was in the fifth month of the CoronaVac vaccination with 41 people. Clinical symptoms of SARS-CoV-2 exposure experienced by participants post the CoronaVac vaccination included pneumonia (3 people), cough and cold (27 people), fever (22 people), myalgia (17 people), and sore throat (11 people). There was no significant relationship p value > 0.05 between gender, age, comorbidities, and Ct value on SARS-CoV-2 exposure post CoronaVac vaccination in health workers at Dr. Saiful Anwar General Hospital, Malang. Conclusion. There was SARS-CoV-2 exposure of 31% post the CoronaVac vaccination in health workers at Dr. Saiful Anwar General Hospital, Malang.